Peak forces and lateral resolution in amplitude modulation force microscopy in liquid - Guzman, Horacio V.; Garcia, Ricardo (Beilstein Journal of Nanotechnology, 2013)
The peak forces exerted on soft and rigid samples by a force microscope have been modeled by performing numerical simulations of the tip motion in liquid. The forces are obtained by using two contact mechanics models, Hertz and Tatara. We present a comparison between the numerical simulations and three analytical models for a wide variety of probe and operational parameters. In general, the forces derived from analytical expressions are not in good quantitative agreement with the simulations when the Young modulus and the set-point amplitude are varied. The only exception is the parametrized approximation that matches the results given by Hertz contact mechanics for soft materials and small free amplitudes. We also study the elastic deformation of the sample as a function of the imaging conditions for materials with a Young modulus between 25 MPa and 2 GPa. High lateral resolution images are predicted by using both small free amplitudes (less than 2 nm for soft materials) and high set-point amplitudes.
Keywords: force microscopy; lateral resolution; nanomechanics; peak force

(untitled) - Gan, Y. (Surf. Sci. Rep., 2009)

(untitled) - Uchihashi, T.; Iino, R.; Ando, T.; Noji, H. (Science, 2011)

(untitled) - Garcia, R.; Magerle, R.; Perez, R. (Nat. Mater., 2007)

(untitled) - Voïtchovsky, K.; Kuna, J. J.; Contera, S. A.; Tosatti, E.; Stellacci, F. (Nat. Nanotechnol., 2010)

(untitled) - Dong, M. D.; Husale, S.; Sahin, O. (Nat. Nanotechnol., 2009)

(untitled) - Raman, A.; Trigueros, S.; Cartagena, A.; Stevenson, A. P. Z.; Susilo, M.; Nauman, E.; Contera, S. A. (Nat. Nanotechnol., 2011)

(untitled) - Xu, X.; Melcher, J.; Basak, S.; Reifenberger, R.; Raman, A. (Phys. Rev. Lett., 2009)

(untitled) - Ando, T.; Uchihashi, T.; Fukuma, T. (Prog. Surf. Sci., 2008)

(untitled) - Martinez-Martin, D.; Herruzo, E. T.; Dietz, C.; Gomez-Herrero, J.; Garcia, R. (Phys. Rev. Lett., 2011)

(untitled) - Rico, F.; Su, C.; Scheuring, S. (Nano Lett., 2011)

(untitled) - Herruzo, E. T.; Asakawa, H.; Fukuma, T.; Garcia, R. (Nanoscale, 2013)

(untitled) - Sader, J. E.; Uchihashi, T.; Higgins, M. J.; Farrell, A.; Nakayama, Y.; Jarvis, S. P. (Nanotechnology, 2005)

(untitled) - Legleiter, J.; Park, M.; Cusick, B.; Kowalewski, T. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Hölscher, H. (Appl. Phys. Lett., 2006)

(untitled) - Lee, M.; Jhe, W. (Phys. Rev. Lett., 2006)

(untitled) - Hu, S.; Raman, A. (Nanotechnology, 2008)

(untitled) - Katan, A. J.; van Es, M. H.; Oosterkamp, T. H. (Nanotechnology, 2009)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Nat. Commun., 2013)

(untitled) - Guzman, H. V.; Perrino, A. P.; Garcia, R. (ACS Nano, 2013)

(untitled) - San Paulo, A.; Garcia, R. (Phys. Rev. B, 2002)

(untitled) - Hu, S.; Raman, A. (Appl. Phys. Lett., 2007)

(untitled) - Xu, X.; Melcher, J.; Raman, A. (Phys. Rev. B, 2010)

(untitled) - Solares, S. D.; Chang, J.; Seog, J.; Kareem, A. U. (J. Appl. Phys., 2011)

(untitled) - Xu, X.; Carrasco, C.; de Pablo, P. J.; Gomez-Herrero, J.; Raman, A. (Biophys. J., 2008)

(untitled) - Garcia, R.; San Paulo, A. (Phys. Rev. B, 1999)

(untitled) - Rodriguez, T. R.; Garcia, R. (Appl. Phys. Lett., 2004)

(untitled) - Solares, S. D.; Chawla, G. (Meas. Sci. Technol., 2010)

(untitled) - Santos, S.; Barcons, V.; Christenson, H. K.; Billingsley, D. J.; Bonass, W. A.; Font, J.; Thomson, N. H. (Appl. Phys. Lett., 2013)

Surface and interfacial forces - Butt, H. J.; Kappl, M. (Wiley-VCH Verlag GmbH & Co. KGaA, 2010)

(untitled) - Tatara, Y. (JSME Int. J., Ser. A, 1993)

(untitled) - Tatara, Y. (J. Eng. Mater. Technol., 1989)

(untitled) - Ikai, A.; Afrin, R.; Sekiguchi, H. (Curr. Nanosci., 2007)

(untitled) - Rodriguez, T. R.; Garcia, R. (Appl. Phys. Lett., 2003)

(untitled) - Kowalewski, T.; Legleiter, J. (J. Appl. Phys., 2006)

(untitled) - Santos, S.; Guang, L.; Souier, T.; Gaderlab, K.; Chiesa, M.; Thomson, N. H. (Rev. Sci. Instrum., 2012)

(untitled) - Vahdat, V.; Grierson, D. S.; Turner, K. T.; Carpick, R. W. (ACS Nano, 2013)

(untitled) - Rodriguez, T. R.; Garcia, R. (Appl. Phys. Lett., 2002)

(untitled) - Voitchovsky, K. (Phys. Rev. E, 2013)

(untitled) - Lozano, J. R.; Garcia, R. (Phys. Rev. B, 2009)

Amplitude Modulation Atomic Force Microscopy - Garcia, R. (Wiley-VCH, 2010)

(untitled) - Florin, E.-L.; Radmacher, M.; Fleck, B.; Gaub, H. E. (Rev. Sci. Instrum., 1994)

(untitled) - O’Shea, S. J.; Welland, M. E.; Pethica, J. B. (Chem. Phys. Lett., 1994)

(untitled) - Han, W.; Lindsay, S. M.; Jing, T. (Appl. Phys. Lett., 1996)

(untitled) - Umeda, N.; Ishizaki, S.; Uwai, H. (J. Vac. Sci. Technol., B, 1991)

(untitled) - Ramos, D.; Tamayo, J.; Mertens, J.; Calleja, M. (J. Appl. Phys., 2006)

Averaging Methods in Nonlinear Dynamical Systems - Sanders, J. A.; Verhulst, F. (Springer, 1985)

(untitled) - San Paulo, A.; Garcia, R. (Phys. Rev. B, 2001)

(untitled) - Lozano, J. R.; Garcia, R. (Phys. Rev. Lett., 2008)

(untitled) - Santos, S.; Verdaguer, A.; Chiesa, M. (J. Chem. Phys., 2012)

(untitled) - Ebeling, D.; Solares, S. D. (Nanotechnology, 2013)